Social interactions, trust and risky alcohol consumption - Abdu Kedir Seid (Health Economics Review, 2016)
Background: The association of social capital and alcohol consumption is one of the most robust empirical findings in health economics of the past decade. However, the direction of the relationship between the two is heavily dependent on which dimension of social capital is studied and which alcohol measure is used. In this paper, we examine the effect of social interactions and generalised trust on drinking in the general Danish population survey. Methods: Participants (n = 2569) were recruited as part of a larger study. The double-hurdle model for the volume of alcohol consumption and the multivariate logistic model for heavy episodic drinking were estimated. Results: We found evidence that social networking with male friends, membership in voluntary organisations, and generalised trust were significantly associated with the mean volume of alcohol consumption and heavy drinking. We also observed that social support at the community level had a buffering effect against heavy episodic drinking. Conclusions: The findings support previous findings in which social interactions and generalised trust were found to predict individuals' volume of drinking and heavy episodic drinking. However, the results varied across the indicators.
Keywords: 330; Risky alcohol consumption; Heavy episodic drinking; Social interaction; Generalised trust